The efficacy analysis of laparoscopic-assisted Soave procedure for Hirschsprung’s disease in neonates and infants within 3 months of age - Renpeng Xia; Tidong Ma; Fan Zhao; Yong Xiao; Yong Feng; Ming Li; Chanjuan Zou; Guang Xu; Chonggao Zhou (Scientific Reports)
Abstract To evaluate the efficacy of laparoscopic-assisted Soave procedure of Hirschsprung’s Disease (HSCR) in neonates and infants within 3 months of age. Patients with HSCR who were admitted to the Department of Fetal and Neonatal Surgery of Hunan Children’s Hospital from June 2012 to July 2020 and underwent laparoscopic-assisted Soave procedure were selected. The clinical manifestations, surgical procedures, postoperative fecal contamination, constipation, enterocolitis, and defecation function were analyzed. A total of 267 children were included, 230 males and 37 females. Vaginal delivery occurred in 138 cases (51.7%) and cesarean delivery in 129 cases (48.3%). There were 217 cases (81.3%) of delayed excretion of meconium, preoperative HAEC (Hirschsprung’s Disease Associated enterocolitis) 116 cases (43.4%), postoperative HAEC 54 cases (20.2%), 1 cases of postoperative death, 266 cases (99.6%) were cured. There were 37 cases (13.9%) of long-segment type, 226 cases (84.6%) of common type, and 4 cases (1.5%) of short-segment type. Of the 267 cases, 214 cases were followed up (80.1%), 60 cases with fecal contamination, the incidence rate was 28.0%, and 5 cases were tertiary fecal contamination. The overall incidence of constipation was 3.7% (8 cases), and 2 cases were third-degree constipation. Evaluation of defecation function: The excellent rate was 94.4%. Laparoscopic-assisted Soave procedure in neonates and infants within 3 months of age is generally safe and feasible, most infants have good postoperative defecation function, and the incidence of postoperative fecal contamination, constipation, and enterocolitis is relatively low.